Using realist review to inform intervention development: methodological illustration and conceptual platform for collaborative care in offender mental health. (December 2015) - Pearson, M.; Brand, S.; Quinn, C.; Shaw, J.; Maguire, M.; Michie, S.; Briscoe, S.; Lennox, C.; Stirzaker, A.; Kirkpatrick, T.; Byng, R.
Abstract Background This paper reports how we used a realist review, as part of a wider project to improve collaborative mental health care for prisoners with common mental health problems, to develop a conceptual platform. The importance of offenders gaining support for their mental health, and the need for practitioners across the health service, the criminal justice system, and the third sector to work together to achieve this is recognised internationally. However, the literature does not provide coherent analyses ofhow these ambitions can be achieved. This paper demonstrates how a realist review can be applied to inform complex intervention development that spans different locations, organisations, professions, and care sectors. Methods We applied and developed a realist review for the purposes of intervention development, using a three-stage process. (1) An iterative database search strategy (extending beyond criminal justice and offender health) and groups of academics, practitioners, and people with lived experience were used to identify explanatory accounts (n  = 347). (2) From these accounts, we developedconsolidated explanatory accounts (n  = 75). (3) The identified interactions between practitioners and offenders (within their organisational, social, and cultural contexts) were specified in a conceptual platform. We also specify, step by step, how these explanatory accounts were documented, consolidated, and built into a conceptual platform. This addresses an important methodological gap for social scientists and intervention developers about how to develop and articulate programme and implementation theory underpinning complex interventions. Results An integrated person-centred system is proposed to improve collaborative mental health care for offenders with common mental health problems (near to and after release) by achieving consistency between the goals of different sectors and practitioners, enabling practitioners to apply scientific and experiential knowledge in working judiciously and reflectively, and building systems and aligning resources that are centred on offenders' health and social care needs. Conclusions As part of a broader programme of work, a realist review can make an important contribution to the specification of theoretically informed interventions that have the potential to improve health outcomes. Our conceptual platform has potential application in related systems of health and social care where integrated, and person-centred care is a goal.